Amartya Sen’s Capability Approach and Education: Enhancing Social Justice - Nadeera Rajapakse (Revue LISA)
Competition, a defining characteristic of Anglo-Saxon capitalist models, has shaped universities. Most higher education policies embrace the instrumental view of education, prioritising the development of human capital, with the ultimate objective of promoting economic growth. Added to this viewpoint, is the perspective of education as a right, which highlights its intrinsic value. This paper suggests that incorporating Amartya Sen’s Capability Approach when assessing higher education provides a broader, multi-criteria framework that answers the need for a normative ideal. Indeed, it focuses on social justice as the metric for evaluating and shaping universities. The paper, therefore, relies on the assumption that education needs to address not only the human capital needs of society, but also the development needs and aspirations of individuals as defined by the Capability Approach. The Capability Approach integrates social justice in the list of priorities and raises additional questions that go beyond the mainstream neoclassical boundary: how can universities contribute towards building a more just society, taking into account human dignity and wellbeing for all. Section one highlights the neoclassical economic theory underlying the competitive higher education models in Anglo-Saxon countries, where the human capital theory prevails. Education is also subject to the overarching cost-benefit analysis methodology, a perspective that is too narrow and instrumental to capture the complex realities it needs to address. Section two elaborates on the theoretical and conceptual insight Sen’s capability approach provides to capitalist economic models in general, and to university education in particular. It considers education as a right, but also as intrinsically important in many other ways. Furthermore, this approach sees the instrumental role of education in ways that surpass the neoclassical view, emphasising its transformative potential.